(untitled) (International Journal of Mathematics and Physics, 2012)
Windmills belong to the most advanced systems, the so-called alternative energy. For example, offshore wind farms today are an important source of renewable energy in many countries, having access to the Baltic and North seas. However, in some regions, especially where the climate is characterized by severe winters, operating manager faced with a very serious problem - the formation of ice on the propeller blades. "At some point the ice with the blade breaks and flies away to a distance of two hundred or three hundred meters, often it is a hefty piece of ice weighing pounds, or even two. Of course, such a bomb might kill. "And these problems are not limited. In the winter for 5 months, employees of Swedish firms were round the clock monitoring of one of the Swedish wind turbines near the city of Herne Sand, measuring wind speed, the thickness of ice on the blades and the performance of wind turbines. It turned out that even a slight crust of ice greatly reduces the efficiency of installation, since the sharp deterioration in the aerodynamic characteristics of blades. As soon as the thickness exceeds one millimeter ldi begin losses. As a result of this wind turbine developed by 15 per cent less electricity. Even if these losses are "scatter" for the entire year, you still get more than 5 percent - a very a significant number. " The problem of an icing relevant for almost all wind turbines: their performance drops significantly in the winter. Not only that, due to the freezing of supercooled rain or sleet worse aerodynamics of the blades, so wind turbines and then have to turn off altogether if the thickness of the ice layer exceeds a critical value. The same situation is observed in Finland and in northern Germany, and Switzerland and Russia. In this work we are considered natural air convection by influence carioles force in direct blade internal hole of Darrieus wind turbine and thermo saving of carousel type wind turbine construction version.